(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to functioning of the word pys’mennyk (writer) as a representative of the concept AUTHOR. Interviews about literature are used as material for research. Ability for combining, shades of meaning, expressive and evaluative load of the word are analyzed. Verbalization of common and individual ideas about writer is accented.